Identifying and Analyzing Factors Influencing Occupational Accidents in the Construction Sector: A Review of 10-year Research - Ghani, Hafid Nur; Ridho, Fiki Muhammad (Pasak: Jurnal Teknik Sipil dan Bangunan, 2024)
The construction sector is one of the industries that has a high risk of occupational accidents. Therefore, preventing accidents from occurring is crucial, one of which is by identifying the factors caused. The present study aims to review articles published in the last 10 years to identify and analyze factors related to the incidence of occupational accidents in the construction sector. A systematic search method was conducted until December 2023 on the following databases: Scopus, ScienceDirect, and Google Scholar. A total of twenty-three articles were included in this review with all articles being original research and discussing factors that contribute to occupational accidents in the construction sector. Our findings show that there are several factors influencing an increase in occupational accidents, namely individual factors, including male gender, younger age, lack of work experience, not long working period, being married, poor level of work safety knowledge, absence of occupational safety training, low level of education, and job dissatisfaction; unsafe action factors, including not using personal protective equipment (PPE) or using inappropriate PPE, not following work safety regulations, applying inappropriate standard operational procedures (SOPs), and fatigue; unsafe condition factors, including the absence of occupational safety and health (OS&H) supervision and inappropriate installation of safety signs; environmental factors, including thermal stress, interference, smooth surfaces, work platform height, and extreme temperature changes during summer and winter; psychological and occupational stress factors, including high time pressure, high workload, poor work schedule, and violence and bullying perpetrated by co-workers or supervisors; and defective equipment factors. In conclusion, individual, unsafe actions, unsafe conditions, environmental, psychological and occupational stress, and defective equipment factors have a significant influence on occupational accidents at construction sites.